Engineering selective pathways for photocatalytic methyl mercaptan oxidation via spatially separated redox centers in Sr-modified carbon nitride - Shanrong Li; Jiali Wang; Shuangqing Liu; Fanghua Zeng; Zhiqi Wen; Rui Xiong; Can Yang (ENGINEERING Environment, 2026)

Unraveling mechanisms of mechanical shear stress-regulated high nitrite production in denitrification: granular structure and metagenomic evidence - Jiarui Fan; Shenbin Cao; Xiangchen Li; Yongzhen Peng; Rui Du (ENGINEERING Environment, 2026)
Partial denitrification granules (PDG) offer a novel approach to supplying nitrite (NO 2 − ) for anammox. Shear stress (τ) induced by mechanical stirring has been recognized as an effective operational strategy for enhancing mass transfer in continuous-flow PDG systems with minimal gas production. However, the effects of shear stress intensity on nitrite (NO 2 − ) accumulation, granular structure, and microbial succession remains unclear. This study established two continuously up-flow PDG systems to assess the influence of low-strength τ (0.2–0.5 Pa) and high-strength τ (1.2–1.4 Pa) on PDG performance under dynamic nitrate (NO 3 − ) loading rates (NLR). Results indicated that low-strength τ promoted the formation of 1–2 mm granules, mitigating the washout of flocs and smaller granules, and sustaining a stable nitrite production rate (NPR) of 7.7 kg N/m 3 ·d) at an NLR as high as 11.7 kg N/(m 3 ·d). In contrast, high-strength τ caused particle fragmentation and reaggregation, accompanied by the washout of sludge containing PD bacteria, leading to a lower NPR of 0.2 kg N/(m 3 ·d). Metagenomic analysis revealed that low-strength τ enhanced nitrogen-carbon metabolism, with Thauera. sp. and Thauera _phenylacetica synergistically driving NO 2 − accumulation. Although high-strength τ promoted the enrichment of Thauera (∼70%), Thauera. sp. decreased its contribution to napA and improved to nirK , whereas Thauera _phenylacetica reduced its contribution to napA , thereby constraining NO 2 − accumulation. These findings provide critical insights into optimizing shear conditions for PDG and enhance the understanding of the metagenomic mechanisms of PD.

A revisit on the enhancing effect of Tween-80 on the bioremediation of PAH-contaminated soil with a surfactant-compatible strain - Likun Zhao; Rui Yue; Hua Li; Shiyu Bao; Chaoqi Chen; Kaihong Chen; Jin Qi; Xuhui Mao (ENGINEERING Environment, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)